Evaluating the Virginia Court-Appointed Special Advocate (CASA) Program, 1991-1995 - Bogle Willard, Trina G. ([Verlag nicht ermittelbar], 2001)
In 1990, the Virginia General Assembly enacted legislation that established the Court-Appointed Special Advocate (CASA) Program, a program providing child advocates in juvenile court proceedings, especially those involving abuse and neglect. The Virginia Department of Criminal Justice Services (DCJS) administered this program. In this capacity, the DCJS coordinated services, provided funds, and participated in the development and dissemination of program information and regulations. Given these responsibilities, DCJS' Juvenile Services Section and the Criminal Justice Research Center Evaluation Section agreed that an assessment of the CASA program was needed. This study sought to evaluate the Virginia CASA program in order to provide a better understanding of CASA activities and program characteristics, and determine the impact of CASA intervention on its client population. Qualitative and quantitative data were collected from three sources: (1) administrative records gathered for a sample of 78 cases (Part 1) involving 164 children (Part 2) taken from the files of local juvenile courts, social service agencies, and CASA programs, (2) telephone interviews administered to judges (Part 3) presiding in all operational CASA jurisdictions across Virginia, and (3) surveys distributed to CASA social workers (Part 4) and volunteers (Part 5). Variables common to both Part 1 and Part 2 include the total number of abuse/neglect, custody, and Children in Need of Supervision/Services (CHINS) petitions, date of first petition, petition type, type of child abuse/neglect case, number and date of prior removals from home, number of out-of-home, group home, psychiatric, detention, and family/friend placements since the case opened, whether there was any alcohol or drug abuse involved, and the onset of these behaviors, whether there were any mental, intellectual, academic, or behavioral limitations or problems, dates of first and last court proceeding, date of finding (a social service agency determination of whether abuse/neglect occurred), permanency date, date of final placement, and the number of weeks a Court-Appointed Special Advocate (CASA) was on the case. Variables unique to Part 1 include the age, sex, and date of birth for up to six victims and up to three abusers, as well as whether any adult or child sibling of the victim had been legally removed from the household, the relationship of each abuser to each victim, and whether any of the victim's siblings, mother, biological father, or caretaker had a criminal history, mental illness, disabilities, or abused drugs or alcohol. Other variables include the number of orders partially or fully complied with or not complied with, the number of services ordered for each victim and abuser, and whether there were any changes in the family structure. For Part 3, judges were surveyed to determine their perceptions regarding the role of CASAs, social workers, and Guardians ad Litem (GALs) in abuse/neglect cases, the benefits of the CASA program, how successful CASA case monitoring was, how useful CASA information was, and the impact CASA programs had on the court process. Judges also recommended changes or improvements they felt were needed by the CASA program that served their court. The percent of abuse/neglect, custody, and CHINS cases that each judge presided over is also included. Demographic variables for Part 4 include the age, sex, and race of each social worker. Other variables cover the length of time worked with CASAs, the number of sexual abuse, neglect, custody, and CHINS cases worked on, and the percent of time used to appear in court, write reports, review records, interview the family and child, and speak with CASAs and GALs. The respondents' perceptions of the role of CASA, social workers, and GALs, how the CASA program was beneficial or detrimental to a child, and suggestions for changes or improvements to the CASA program complete the file. Variables for Part 5 include the number of physical abuse, neglect, custody, and CHINS cases worked on by a CASA volunteer. Additional variables include the percent of time used to investigate and monitor the child, family, foster family, the GALs, the social worker, and other CASA staff, as well as the volunteer's relationship with social workers, GALs, and judges. The age, sex, race, and educational background of each volunteer are also included.